The Impact of Microfinance Services on Socio-Economic Welfare of Urban Vulnerable Households in Malaysia - Her-Loke Koh; Sakiru Adebola Solarin; Yee-Yen Yuen; Suganthi Ramasamy; Guan-Gan Goh (International Journal of Business and Society, 2021)
The main objective of this study is to examine the effect of microfinance services on the socio-economic welfare of urban households in Malaysia. We distribute questionnaires to 400 respondents across three different urban areas in Malaysia in order to collect the relevant data for this study. Quota sampling is employed in the process of collecting the data. Incorporating income as a mediating variable into the model, the results show that most of the services provided by the microfinance institutions including microcredit, micro insurance and training have significant effect on socio-economic welfare. Income is also observed to have a significant impact on socio-economic welfare. With the exception of training, the microfinance services also have significant impact on income. The results further show that most of the microfinance services have indirect effect on welfare through income. The recommendations of this study are detailed in the body of the paper.